2023
DOI: 10.1136/bmjopen-2022-067752
|View full text |Cite|
|
Sign up to set email alerts
|

Healthcare waste management practice and its predictors among health workers in private health facilities in Ilu Aba Bor Zone, Oromia region, South West Ethiopia: a community-based cross-sectional study

Abstract: ObjectivesA lack of safe healthcare waste management (HCWM) practice poses a risk to healthcare staff, patients and communities. In low-income countries like Ethiopia, studies on the level of safe HCWM practices in private healthcare facilities are limited. This study was designed to assess the level of good HCWM practice and associated factors among health workers in private health facilities.MethodsAn institution-based cross-sectional study was conducted in the Ilu Aba Bor zone, South West Ethiopia. A random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The gap in awareness about these essential documents can adversely affect enforcement and compliance to these stipulated guidelines. To buttress the importance of knowing a health-care waste management guideline [ 13 ], found out that health workers who had read a waste management guideline were four times better in managing medical wastes than their counterparts who had not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gap in awareness about these essential documents can adversely affect enforcement and compliance to these stipulated guidelines. To buttress the importance of knowing a health-care waste management guideline [ 13 ], found out that health workers who had read a waste management guideline were four times better in managing medical wastes than their counterparts who had not.…”
Section: Resultsmentioning
confidence: 99%
“…It has been estimated globally that one in every three health-care facilities do not practice safe medical waste management [ 13 ]. In combatting these dangerous repercussions associated with mismanagement of hospital wastes, efforts have been made by various countries in developing national health care management policies.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [14] found that knowledge about water conservation predicted farmers' behavior to conserve water. In addition, several empirical studies have shown that lack of knowledge about waste management has a negative impact on effective waste management [69][70][71]. However, Thakur and Onwubu [72] found no significant relationship between waste management knowledge and awareness, TPB constructs, or waste management intentions in South Africa.…”
Section: Water Waste Reduction-related Knowledgementioning
confidence: 99%